Problems in Enforcing the Liquor Prohibition Regulation - Wahib, Moh.; Rohman , Baitur; Irawati, Dewi (Fakultas Syariah Institut Agama Islam Negeri Lhokseumawe, 2025)
Enforcing local regulations prohibiting alcoholic beverages in Papua is a complex challenge that requires a comprehensive understanding of the legal framework, law enforcement practices, and community dynamics. This study aims to analyze the challenges of enforcing the prohibition of alcoholic beverages in Papua Province. The researcher seeks to explore the substance of the prohibition of alcoholic beverages in Papua Regulation No. 15 of 2013 and its legal status within the Indonesian legal framework. The results of the study reveal that the substance of Papua Regulation No. 15 of 2013 is to completely ban the production, distribution, sale, and consumption of alcoholic beverages. This legal status is legally contrary to the principle of the hierarchy of laws based on the principle of